Pengaruh Token Ekonomi Untuk Menurunkan PerilakuAgresif pada Anak Sekolah Dasar - NAJMUDIN, MUHAMMAD IMAM (2011)
This research aims to determine the effect of token economy on An aggressive behavior in children elementary school age. Aggressive behavior is attacking others both verbally and physically that aims to hurt others or harm to others who do not desire the behavior is happening to him.Token economies are a form of behavior modification designed to change the desired behavior by gathering evidence or signs, which can be swapped for something desired according to the requirements that have been determined.Participants in this research were eight children elementary school age, who is male sex, acquired from the elementary school in Surakarta. This research uses eksperimental type of Small-N research design. With the model ABCB-Folow up, which is twice the application of the treatment. The treatment used is the token economy, which is using bank token,where each student was given a savings as much as one hundred.During four days of treatment students are observed if there are one of the students who perform aggressive behavior then the student receives a predetermined amount of points according to thebehaviors performed. Implementing this research is the teacherassisted by the three observers who had been briefed in advance.While the measure in this study is Behavior check-list. The collected data were analyzed using statistical calculation was done by t-test using SPSS. Values ob s this study received, statistical calculation was done by t-test using SPSS. Values obtained from sta are very significant, which means that the hypothesis in this study received. In addition In addition to visual analysis, which is based on the graphs presented. The numbers marked on the chart are the numbers obtained from the average of observations from three observers. Based on the analysis results obtained that the average score of aggressive behavior has decreased, a decrease in scores between, the baseline phase, and the first treatment as much as 5.8, the re- phase observation and the second treatment happens a decrease of 1.2. Conclusions in this study that the token economy to effectively reduce aggressive behavior in elementary school students.